If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-14 + 4y) + -2y = 14 (-14 * 4 + 4y * 4) + -2y = 14 (-56 + 16y) + -2y = 14 Combine like terms: 16y + -2y = 14y -56 + 14y = 14 Solving -56 + 14y = 14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 14y = 14 + 56 Combine like terms: -56 + 56 = 0 0 + 14y = 14 + 56 14y = 14 + 56 Combine like terms: 14 + 56 = 70 14y = 70 Divide each side by '14'. y = 5 Simplifying y = 5
| 4(20x+50)=840 | | 2k-6k=3(7-2k)-7(8k+3) | | 4.5b-5.25b+3=3.75 | | (x^2-2x-2)(x^2-12x+37)=0 | | y=9.5(20)+100 | | 12x=46-6x | | 50-3x=15+2x | | 4.5+5.25+3=3.75 | | 4x+17=-2x+3 | | 2x^2-14=-64 | | 3x-5=6x-5 | | 92-20=9h | | y=9.5x+100 | | n+0.5=-2.833 | | 4.5b-5025b+3=3075 | | 15=-6+4(d+3) | | -16-t=7 | | (3-2x)=7 | | 6+6x-10=-20 | | 6x-10x=10x-10x-2 | | -17r+8=42 | | -4(3x+3)=7x-2 | | 2y=-172-6x | | -4h+8=36 | | 3(2x+3)=4(x-6) | | 2-.33x=26 | | 18(6m+7)=-9(8m+6) | | 8s+16=4 | | .5x+6=18 | | -10.25y=-9.33 | | 2y=172-6x | | 6d+3d+6d+7-5d=0 |